Reactivity-promoting criterion based on internal vibrational energy redistribution - Mitrić, Roland (National Academy of Sciences, 2007)
We propose to introduce intrinsic dynamical properties as a criterion for promoting reactivity of small size noble metal reactive centers relevant for heterogeneous catalysis. To illustrate the concept, collisions between Ag(6)(−) or Au(6)(−) clusters and molecular oxygen have been investigated with direct ab initio molecular dynamics by using DFT. We show that different nature and efficiency of internal vibrational energy redistribution (IVR) during reaction dynamics is responsible for significantly different sticking probabilities of O(2) to gold and to silver clusters. In the case of Au(6)(−) and O(2) collisions, resonant IVR occurs between two subunits activating O(2) and promoting subsequent oxidation reactions. In contrast, a dissipative IVR in Ag(6)(−) and O(2) molecule prevents O(2) to react with other adsorbates. These findings allow us to introduce the nature of IVR as a criterion for promoting the reactivity of noble metal clusters: Resonant IVR between reactants promotes reactivity toward adsorbates.